[P114] Effective dose for medical workers during Y-90 microshperes radioembolization. (August 2018) - Dalianis, Konstantinos; Koutsouveli, Efi; Vlachou, Fani; Pipikos, Theodoros; Kollia, George; Prasopoulos, Vasilis
Abstract : Introduction: Due to the increasing need for radioemblization of liver cancer with Yttrium 90 microspheres a new need for evaluation of the radiation exposure of the medical staff is necessary. The objective of this study is to assess occupational exposure for nuclear medicine, radiology and clinical staff involved in Y 90 preparation and implantation. Although there are guidelines and regulation regarding the use of radioisotopes for therapy when a new teaqnic is used for first time new measurements should be perform in order to reduce the occupational radiation doses to the workers. Material & Method: To estimate the effective dose from external exposure the nuclear medicine physician and the medical physicist had electronic dosimeters and TLD badges worn at the upper pocket of their overall, TLD rings on the second finger of each hand. The basics stages for radioemblization procedures involve 3 steps: measuring the Y-90 vial, segmentation of the dose, transport to radiology, implantation of the radiopharmaceutical. Results: The results of our study for the average cumulative whole body dose for 22 patients ( μ Sv  ±  SD) at different stages were: measuring the Y-90 vial, segmentation of the dose, transport to radiology, 132  ±  7, 23 (Medical Physicist), implantation of the radiopharmaceutical 197  ±  6, 67 (Nuclear Medicine Physician). The mean finger exposures for the Medical Physicist were 132  ±  76  μ Sv/GBq. For administration of resin microspheres, mean finger exposures for the Nuclear Medicine Physician were 197.5  ±  90  μ Sv/GBq. Conclusion: Medical staff performing radioembolization procedures is exposed to safe levels of radiation. The personnel dose results are significantly lower than the recommended annual dose by International Commission for Radiological Protection. However a greater effort should be made to reduce the doses further in line with the ALARA principle.